OFF THE SHELF. (Calliope, 2013)
The article offers information on two books including "Marathon: How One Battle Changed Western Civilization," by Richard A. Billows and "The Silence of Our Friends: The Civil Rights Struggle Was Never Black and White," by Mark Long & Jim Demonakos and a series of DVDs of science reality show.